KAPABILITAS PEMERINTAH KOTA PEKANBARU DALAM MERESPON PROSTITUSI MENGGUNAKAN SARANA MEDIA ONLINE TAHUN 2020-2022 - Eka Novriadi Saputra; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study is motivated by the capability of the Pekanbaru City government in responding to community diseases. It's modern in the use of technology that has a negative impact on society, through the MiChat application, many women sell services called Open BO. So that news circulated about the rise of prostitution using online media facilities in Pekanbaru City under the guise of massage parlors. This study uses the theory of Government Organizational Capability according to Kusumasari which has indicators 1) Institutional 2) Human resources 3) Policy 4) Finance 5) Technical resources 6) Leadership. This study seeks to determine the capability of Pekanbaru City in responding to prostitution using online media facilities in 2020 - 2022. This research uses a qualitative approach with a descriptive method. In collecting data, the writer uses interview and documentation techniques. The results of the study explain that the capacity of the Pekanbaru City Government in responding to prostitution uses online media facilities, in collaboration with the Civil Service Police Unit, the Social Service, and the Ministry of Communication and Information. The Civil Service Police Unit carried out raids on hotels, boarding houses, guest houses and other places where prostitution was arranged using online media. After being secured by the Civil Service Police Unit, they were taken to the Civil Service Police Unit office for data collection and then taken to the Pekanbaru City Social Service shelter to carry out rehabilitation or coaching. The Ministry of Communication and Informatics in its role conducts education regarding the wise use of the internet and social media wisely so as not to fall into prostitution using online media facilities. Keywords: Capability, Societal Diseases, Online Prostitution